Pengaruh Aplikasi Pupuk Kascing Terhadap Beberapa Sifat Fisika Tanah Inceptisol dan Pertumbuhan Tanaman Rambutan - Sidik, Ikhsan; Syaf, Hasbullah; Leomo, Sitti; Hemon, Tufaila; Alam, Syamsu; Rustam, La Ode (Jurnal Agroteknologi (Agronu), 2024)
One of the efforts to increase productivity and improve the physical properties of Inceptisol soil is by applying organic fertilizer in the form of vermicompost. This study aims to determine; (1) The effect of vermicompost fertilizer on several physical properties of Inceptisol soil; (2) The effect of vermicompost fertilizer on the growth of rambutan plants in Inceptisol soil; (3) The dose of vermicompost fertilizer has a better effect on the physical properties of the soil and the growth of artificial plants. This research was carried out in the community garden of Amohalo Village, Konda District, South Konawe Regency, Southeast Sulawesi Province and lasted for 6 months, starting from May to October 2022, using a Randomized Block Design (RAK), with 6 levels of vermicompost fertilizer treatment. treatment and 4 repetitions. Data analysis in this study uses variance and if there is a real effect, it is continued with the BNJ test at a confidence level of 95%. Research variables include soil (bulk density, soil porosity, aggregate stability) and plants (height and number of leaves). The results of this study showed that the variable plant height had a significant effect at the age of 17-21 MTs and a very significant effect at the age of 23 MTs. While the variable number of leaves had a real effect at the age of 17 and 21 weeks after planting. It can be concluded that if (1) Vermicompost is able to increase aggregate stability, reduce unit weight and increase the porosity of Inceptisol Soil; (2) Vermicompost fertilizer has a real influence on the growth of rambutan plants in Inceptisol soil; (3) The dose of Vermicompost Fertilizer that has a better effect on the physical properties of the soil and the growth of artificial plants is in the 2.5 kg treatment.